Development of a Kahoot-Based Evaluation Tool to Increase Learning Motivation of X IPS Students of SMAN 1 Blega Bangkalan - Ningsih, Fitria; Mariatun, Ika Lis; Arief, R. Zaiful (FKIP - Universitas Riau, 2022)
This study is a research on product development of learning evaluation media based on Kahoot Social Studies lesson management material in class X SMAN 1 Blega Bangkalan. This study aims to (1) determine the media evaluation tool based on kahoot learning in class X student management materials. (2) Knowing the media motivation of Kahoot-based learning evaluation tool on management material in class X (3) Knowing the improvement of student X's learning on management material by using kahoot. This development research was conducted using the ADDIE model which consisted of several stages, namely analysis, design, development, implementation and evaluation. Based on this research, for the assessment of material experts, media experts, field practice (teachers) the percentage score of the material aspect is 72% with the (adequate) category, the media aspect is 80% with the (adequate) category, the field practice (teacher) aspect of 100% with the category (Very Eligible). Based on the response of students' learning motivation, it was initially increased by 1850 after using the learning evaluation tool media through kahoot by 2211, experiencing an increase in the number of 361.